2023
DOI: 10.3390/ijms24098372
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Intrinsic Visible Fluorescence Emitted by Peptide/Protein Amyloid-like Assemblies

Abstract: Amyloid aggregation is a widespread process that involves proteins and peptides with different molecular complexity and amino acid composition. The structural motif (cross-β) underlying this supramolecular organization generates aggregates endowed with special mechanical and spectroscopic properties with huge implications in biomedical and technological fields, including emerging precision medicine. The puzzling ability of these assemblies to emit intrinsic and label-free fluorescence in regions of the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 139 publications
0
9
0
Order By: Relevance
“…The change of intrinsic fluorescence of Aβ peptides offers valuable information about the structure, folding, and dynamic of these molecules. The effect of complexes 1 and 2 on the autofluorescence of amyloid aggregates formation was evaluated by recording fluorescence emission spectra over time (Figure ). The native Aβ 1–42 exhibits a time dependent increase of emission intensities with maxima centered at two different wavelengths: 478 and 517 nm, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The change of intrinsic fluorescence of Aβ peptides offers valuable information about the structure, folding, and dynamic of these molecules. The effect of complexes 1 and 2 on the autofluorescence of amyloid aggregates formation was evaluated by recording fluorescence emission spectra over time (Figure ). The native Aβ 1–42 exhibits a time dependent increase of emission intensities with maxima centered at two different wavelengths: 478 and 517 nm, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The autofluorescence assay of amyloid systems is becoming a valuable tool to evaluate the modulatory effects of chemical agents during aggregation. 40 The effects of Ru 2 complexes on the autofluorescence of the Aβ 1−42 peptide were evaluated by recording fluorescence emission spectra over time at different excitation wavelengths in the absence and presence of the diruthenium complexes (Figure 2). As anticipated, excitation at 390 nm results in an increase of emission intensity at 478 nm after 48 h (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…MD studies demonstrated that the interconnected fibrillary networks are originated by the capability of these peptides to opportunely arrange by forming two interfaces: a wet and a dry one. In the attempt to identify novel materials with enhanced and unexpected properties, we punctually replaced the original, natural amino acids with the non-natural ones like Nal and Dopa . The effect of these modifications and of the PEG moiety at the N-terminus of the peptides were evaluated. , …”
Section: Discussionmentioning
confidence: 99%